Concentration-dependent dye aggregation and disassembly triggered by the same artificial helical foldamer. (29th April 2019) - Qiu, Yuan; Hu, Haisi; Zhao, Dongxu; Wang, Jing; Wang, Hong; Wang, Qin; Peng, Haiyan; Liao, Yonggui; Xie, Xiaolin
Abstrct: Constructing and regulating the cyanine dye aggregates have been constantly pursued because of their wide applications in photosensitizers, biological fluorescence probes, nonlinear optics, etc. However, to realize such a process using a single additive still remains a formidable challenge. Here, the aggregation and disassembly of positively charged 3, 3-diethyloxadicarbocyanine iodide (DiOC 2 (5) ) have been demonstrated just by changing the concentration of an artificial poly(phenylenediethynylene)-based helical foldamer (Poly-1 ) bearing L-alanine sodium pendants with an amide linker.Poly-1 possessed the negatively charged pendants and hydrophobic helical grooves. Upon simple mixing of equalDiOC 2 (5) andPoly-1, DiOC 2 (5) molecules were mainly enriched onPoly-1 surface driven by electrostatic interaction and arranged along the main chain ofPoly-1, resulting in the formation of chiral H-aggregates. But, the excessivePoly-1 would attract someDiOC 2 (5) molecules in H-aggregates via electrostatic interaction. The isolated monomers were easy to orderly disperse into the helical grooves due to hydrophobic interaction. Meanwhile, during the aggregation and disassembly, the solution color changed from peachblow to purple red and then to purple and finally to navy blue. Graphical abstract: Image 1 Highlights: A novel strategy to achieve chiral H-aggregation and disassembly of cyanine dyes via changing [foldamer]/[dye] ratio. The new foldamer contains multiple binding sites, i.e., negatively charged pendants, helical grooves and cavities, for dyes. During the aggregation and disassembly, the solution color changes from peachblow to navy blue.